HUBUNGAN KADAR GULA DARAH DAN TEKANAN DARAH TERHADAP FUNGSI KOGNITIF LANSIA DI KELURAHAN MERUYA, JAKARTA BARAT - Magistra Cylvia Margaretha; Yuda Turana; Jimmy Barus; Nelly Tina Widjaja (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: A decline in cognitive function in the elderly occurs in the body due to aging. Internal and external factors influence the decline in cognitive function in the elderly. This research focuses on blood sugar, blood pressure, and the elderly's characteristics as a factor in decreasing the cognitive function of the elderly.Methods: This research uses the descriptive-analytic method with a cross-sectional design of 101 respondents. The independent variables of this study are blood sugar, blood pressure, and demographic characteristics. The dependent variable is the cognitive function of the elderly. Data obtained were analyzed both univariate and bivariate using the Chi-square test.Results: Blood pressure has a significant relationship with the impaired cognitive function in the elderly (p<0.05). Other factors, such as blood sugar, age, sex, and education level did not show any relationship with the cognitive function of the elderly (p>0.05).Conclusion: Blood pressure has a relationship with cognitive function in the elderly. In contrast, blood sugar does not have a relationship with cognitive function.